Zanikana neenakost - Pajnik, Mojca (Teorija in praksa, 2017)
Based on analysis of the media system in Slovenia, in the article we find that media policy in the last 25 years has not paid the necessary attention to gender equality. We proceed from the thesis that gender-sensitive media policy has positive effects for the positions of management personnel in the media and, on the contrary, that gender-insensitive media policy is reflected in the positions and values of employees in management structures. This thesis is verified in the article by analysing the situation of the Slovenian media environment. We base the empirical data on 12 interviews with leading staff at three television stations in Slovenia and with representatives of professional associations. The interview analysis shows how media workers occupying leading positions in thinking about gender inequality adopt what we call "the principle of minimising the role of gender" when respondents contend that inequalities do not exist, by which they actually accept and justify them. At the same time, the results show there is considerable homogeneity in the views of management that discrimination according to gender is not a problem, that it does not exist or that the only thing that is relevant in the media is the individual's "own motivation and work". The article points to some new mechanisms of gender differentiation that are appearing in the media industry through practices and attitudes that take on awareness of the importance of equality, which is at the same time denied by use of different denial and minimisation strategies.
Keywords: Mass media; Mass media policy; Medijska politika; Množični mediji; Sex differentiation; Sex discrimination; Slovenia; Slovenija; Spolna diferenciacija; Spolna diskriminacija; Television; Televizija; vodstveni delavci